Choline Chloride – Citric Acid Monohydrate Based Deep Eutectic Solvents As Alternative Media For Averrhoa Bilimbi Pectin (Abp) Extraction And As Plasticizers For Abp Bioplastic - Shafie, Muhammad Hakimin (2021)
Averrhoa bilimbi is an abundance and underutilized fruit. The extraction of pectin using strong acids and mineral acids produce hazardous effluents and low yield, respectively. Therefore, A. bilimbi fruit was suggested to be a good source of pectin whereas the deep eutectic solvent (DES) was suggested to be an environmental friendly and highly efficient medium for A. bilimbi pectin (ABP) extraction and as an alternative plasticizer for bioplastic (BP) production. The choline chloride – citric acid monohydrate based DES at different molar ratios (i.e. 3:1, 2:1, 1:1, 1:2 and 1:3) were successfully synthesized and DES 1:1 was found to meet the eutectic point. Results showed that increasing the molar ratio of citric acid monohydrate in DES, higher values of viscosity, surface tension and density were observed. Subsequently, these DESs were used as a medium for extraction of ABP. The result showed that DES-assisted extraction process required shorter time (30 minutes less) than citric acid monohydrate and the yield was higher (4.96% more) with optimal condition of 3.74% (w/v) of DES, an extraction temperature of 80 °C, and extraction time of 2.5 h. Apart from that, ABP-CAM was found lower in linearity with higher branch size of the pectin than ABP-DES. It was also observed that using DES as the extraction medium had improved the water and oil holding capacities (4.25 and 101.69%, respectively), foaming capacity (6.19%) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity (43.56%) compared to ABP-CAM.